2023
DOI: 10.23736/s1973-9087.22.07813-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment, anxiety and depression: a map of Cochrane evidence relevant to rehabilitation for people with post COVID-19 condition

Abstract: INTRODUCTION Currently, no evidence exists on specific treatments for post COVID-19 condition (PCC). However, rehabilitation interventions that are effective for similar symptoms in other health conditions could be applied to people with PCC. With this overview of systematic reviews with mapping, we aimed to describe the Cochrane evidence on rehabilitation interventions proposed for cognitive impairment, anxiety and depression in different health conditions that can be relevant for PCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…However, due to the immense workload, they often cannot get sufficient time for recovery before returning to the hospital, leading to prolonged exhaustion. Furthermore, a substantial body of previous research has also confirmed that health condition was a significant contributing factor to various emotional disorders (50)(51)(52)(53)(54). Therefore, health condition was also a crucial factor contributing to burnout among healthcare workers during this period.…”
Section: Discussionmentioning
confidence: 86%
“…However, due to the immense workload, they often cannot get sufficient time for recovery before returning to the hospital, leading to prolonged exhaustion. Furthermore, a substantial body of previous research has also confirmed that health condition was a significant contributing factor to various emotional disorders (50)(51)(52)(53)(54). Therefore, health condition was also a crucial factor contributing to burnout among healthcare workers during this period.…”
Section: Discussionmentioning
confidence: 86%
“…Patients with psychiatric and mood disorders very often suffer from cognitive deficits. Learning and memory impairments occur in patients with schizophrenia [ 70 , 71 , 72 ] as well as in depressed patients and people with anxiety [ 73 , 74 , 75 , 76 , 77 ]. Therefore, we examined the potential procognitive and anti-amnesic effects of JJGW07 in the passive avoidance task in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Cordani et al published a Cochrane Systematic review of rehabilitation for people with PCC with cognitive impairment, anxiety, and depression, which included 17 reviews on cognitive impairment and 37 on anxiety and depression. As a result, they found that acupuncture was effective (very low- to moderate-quality evidence) for the rehabilitation of specific diseases [ 27 ].…”
Section: Discussionmentioning
confidence: 99%